2008
DOI: 10.1177/0003319707305345
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Investigation of a Giant Splenic Artery Aneurysm

Abstract: Splenic artery aneurysms represent approximately 60% of visceral arterial aneurysms. Their incidence at autopsy is 0.02 - 2 % in all age groups and rises to 10.4% above the age of 60. Although splenic artery aneurysms are the most common visceral aneurysms, giant splenic artery aneurysms >10 cm in diameter have rarely been reported. A recent review of the literature came up with 12 true giant splenic artery aneurysms >10 cm. A case of 12-cm splenic artery aneurysms is presented in this study and the imaging fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…The incidence of SAA among patients with a diagnosis of cirrhosis and portal hypertension varies from 7 to 50%, and PHT is diagnosed in 50% of SAA patients. 3 , 18 , 33 Hormonal changes during pregnancy and increased splenic artery outflow might contribute to either the improvement of a new aneurysm, enlargement of a preexisting lesion, or rupture of an aneurysm. 7 , 14 , 18 The third trimester of pregnancy is the period with the highest risk.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SAA among patients with a diagnosis of cirrhosis and portal hypertension varies from 7 to 50%, and PHT is diagnosed in 50% of SAA patients. 3 , 18 , 33 Hormonal changes during pregnancy and increased splenic artery outflow might contribute to either the improvement of a new aneurysm, enlargement of a preexisting lesion, or rupture of an aneurysm. 7 , 14 , 18 The third trimester of pregnancy is the period with the highest risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an intraperitoneal hematoma filling the gap between the spleen and stomach can also be seen. arterial aneurysms, and Vlychou et al [1] found that they had an incidence rate of between 0.02 and 2% in a large autopsy series that included all age groups. Moreover, the third most common abdominal aneurysm is an SAA.…”
Section: Discussionmentioning
confidence: 98%
“…Splenic artery aneurysms (SAAs) are relatively rare, even though they are the most common of the visceral aneurysms and the third most common intraabdominal aneurysms after aortic and iliac. [1,2] They may result from a congenital weakness of the arterial wall, pregnancy, portal hypertension (HT), or atherosclerosis. [3] The great majority of SAAs are asymptomatic and are diagnosed incidentally on imaging studies.…”
mentioning
confidence: 99%
“…SAA is a rare pathology with an incidence estimated at 0.01% in the general population with incidence at autopsy shown to be 0.2%–2% 1. Above the age of 60 years this incidence has been shown to increase to 10% in general, with figures approaching 50% in patients with portal hypertension 1 2. True aneurysms are usually asymptomatic, in contrast to pseudoaneurysm which have a reported rate of rupture of 37%–47%, with devastating consequences 3–5.…”
Section: Introductionmentioning
confidence: 99%